2019
DOI: 10.1101/843052
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effective Combination Immunotherapy using Oncolytic Viruses to Deliver CAR Targets to Solid Tumors

Abstract: Chimeric antigen receptor (CAR)-engineered T cell therapy for solid tumors is limited by the lack of tumor-restricted and homogeneous expression of tumor antigens1,2. Therefore, we engineered an oncolytic virus to express a non-signaling, truncated CD19 (CD19t) protein for tumor-selective delivery, enabling targeting by CD19-specific CAR T cells. Infecting tumor cells with a chimeric oncolytic vaccinia virus coding for CD19t (OV19t) produced de novo CD19 surface-antigen expression prior to virus-mediated tumor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…The typhoid fever vaccine Vi-DT (International Vaccine Institute) was well tolerated and immunogenic in children aged 6-23 months in a Phase 2 trial. 6 Both one-and two-dose regimens induced comparable seroconversion rates. The vaccine consists of the Vi polysaccharide from Salmonella Typhi conjugated to diphtheria toxin.…”
Section: Typhoid Conjugate Vaccine Is Safe An Immunogenic In Young Chmentioning
confidence: 97%
“…The typhoid fever vaccine Vi-DT (International Vaccine Institute) was well tolerated and immunogenic in children aged 6-23 months in a Phase 2 trial. 6 Both one-and two-dose regimens induced comparable seroconversion rates. The vaccine consists of the Vi polysaccharide from Salmonella Typhi conjugated to diphtheria toxin.…”
Section: Typhoid Conjugate Vaccine Is Safe An Immunogenic In Young Chmentioning
confidence: 97%
“…Examples for oncolytics/CAR T cell therapy combinations include the administration of oncolytic viruses encoding BiTEs, cytokines, and/or checkpoint inhibitors, [271][272][273] or oncolytic viruses that encode CAR targets. 274,275 In addition, investigators have explored the use of T cells to directly deliver viruses into tumors. [276][277][278] Checkpoint blockade/ CAR T cell therapy combinations are actively being pursued, 279 including the aforementioned clinical studies combining mesothelin-CAR T cells with pembrolizumab for the treatment of mesothelioma.…”
Section: Combinatorial Therapiesmentioning
confidence: 99%
“…The combination of HER2/neu (also known as ErbB-2) CAR-T cells and oncolytic adenovirus-expressing anti-PD-L1 and IL-2 remarkably improved survival compared with either form of therapy alone in head and neck squamous cell carcinoma xenograft mice [ 71 ]. Moreover, Park et al reported a novel therapeutic combination using both OVs and CAR-T therapy in their recent study [ 72 ]. They used an oncolytic chimeric orthopoxvirus carrying CD19t (OV19t) to generate CD19t at the tumor cell surface.…”
Section: Ov Combination Immunotherapymentioning
confidence: 99%
“…They used an oncolytic chimeric orthopoxvirus carrying CD19t (OV19t) to generate CD19t at the tumor cell surface. After the administration of the OV19t and CD19-CAR T cell combination, ~70% of tumor cells were positive for CD19t and showed increased CAR-T cell infiltration in human tumor (MDA-MB-468) xenograft mice [ 72 ]. These preclinical studies suggest the promising potential of this combination therapeutic strategy for cancer treatment.…”
Section: Ov Combination Immunotherapymentioning
confidence: 99%